Letters. (Computer (00189162), 2012)
Letters to the editor. This column also includes an erratum correcting the labeling of the y-axis in Figure 5a in "SimWare: A Holistic Warehouse-Scale Computer Simulator" (10.1109/MC.2012.251), S. Yeo and H.-H.S. Lee, Computer, Sept. 2012, pp. 48-55.